Clean and green organizing in urban neighborhoods: Measuring perceived and objective outcomes. Issue 3 (2nd October 2019) - Mattocks, Nicole; Meyer, Megan; Hopkins, Karen M.; Cohen-Callow, Amy
ABSTRACT: One way in which urban community organizations attempt to improve neighborhood health is through cleaning and greening efforts. Few studies have evaluated how such efforts are related to changes in both residents' perceptions of neighborhoods and objective community-wide cleaning and greening indicators over time. Drawing upon quantitative and qualitative data collected during an evaluation of a community-building initiative in two communities, results show how neighborhood changes in cleaning and greening were reflected in perceived and objective measures and how these measures compare across different time periods and sub-groups of residents within the two target communities. We provide suggestions for additional ways that future evaluations of urban cleaning and greening efforts can examine the impact.